Regionaliatión of Monthly Flows of the Titicaca Hydrographic Region, Perú - Lujano Laura, Apolinario (2017)
This research was conducted in the Hydrographic Region Titicaca, Peru. The main objective was to develop regional models of average monthly flows and persistence of the main rivers, applied to the problem of estimation of flows in basins without hydrometric registration. The climatic and physiographic characteristics of the basins under study were taken as independent variables and the mean monthly flows and persistence as a dependent variable. The methodology to identify homogeneous hydrological regions was made through the techniques of Ward and L-Moments. The regional equations were determined using potential regression models, the explanatory variables being the basin area and the length of the main river. The Nash-Sutcliffe (NSE) efficiency indicators and the root mean square error (RMSE) were used to assess the statistical significance of the regional models. The proposed regional equations show a good performance and estimate the observed flows.